PENGARUH FAKTOR PENGETAHUAN DAN MOTIVASI TERHADAP KEPATUHAN SERTA KEBERHASILAN TERAPI PADA PASIEN TUBERKULOSIS PARU RAWAT JALAN - Clara Ritawany Sinaga; Esty Elvinda; Annafiatuzakiah; Juarita Injiliani (Jurnal Ilmiah Manuntung: Sains Farmasi Dan Kesehatan, 2026)
Pulmonary tuberculosis (TB) remains a major public health problem in Indonesia, with a high disease burden and treatment success that largely depends on patient adherence. Non-medical factors such as knowledge and motivation are believed to play important roles in improving adherence and treatment outcomes; however, simultaneous analyses of these factors remain limited, particularly in East Kalimantan. This study aimed to analyze the influence of knowledge and motivation on adherence and their impact on treatment outcomes among pulmonary TB outpatients. A quantitative analytic observational study with a cross-sectional approach was conducted among 84 pulmonary TB outpatients at RSUD Abdoel Wahab Sjahranie Samarinda (June–July 2024). Data were collected using a knowledge questionnaire (Guttman scale), a motivation questionnaire (Likert scale), and the MARS-5 adherence instrument, along with medical record data for treatment outcomes. Data were analyzed using the chi-square test and logistic regression. The majority of respondents had good knowledge (83.3%), good motivation (50%), and moderate adherence (53.6%). Treatment outcomes showed that 85.7% of patients were cured. A significant association was found between knowledge and adherence (p = 0.004). Overall, knowledge and motivation contributed to improved adherence, which subsequently affected treatment success. A holistic approach integrating improvements in patient knowledge and motivation is essential for enhancing adherence and treatment outcomes in pulmonary TB. These findings support strengthening educational and motivational interventions by healthcare professionals to optimize treatment success among pulmonary TB outpatients.